PUBLIC RELATIONS IN POSTCRISIS RECOVERY: ANALYSING NIGERIA'S GOVERNMENT COMMUNICATION IN THE SECURITY SECTOR - Garba, Suleiman (African Journal of Social and Behavioural Sciences, 2024)
This study analyses the role of public relations (PRs) in postcrisis recovery, with a focus on the Nigerian government’s communication strategies in the security sector. In the face of persistent security challenges such as insurgency, terrorism, and communal violence, Nigeria’s recovery efforts are often hindered by inadequate crisis communication. Effective PR strategies are vital for restoring public trust, rebuilding institutional credibility, and fostering social cohesion during the postcrisis period. This study uses established crisis communication frameworks to explores how PR can be strategically employed to manage government communication after a crisis, especially in a fragile security environment. The research employed a qualitative approach, relying on secondary data sources, including journal articles, reports, and official documents. Key findings indicate that while the Nigerian government recognises the importance of communication in postcrisis recovery, existing PR strategies are often fragmented and lack coherence, consistency, and transparency. The study concludes that a more integrated and proactive PR approach is essential for improving government credibility and fostering sustainable peace. Recommendations include the need to develop tailored PR strategies that incorporate local contexts, enhance collaboration between government agencies and the media, and prioritise transparency in all communication efforts.